Influence Islamic Curriculum Family and School to Character Student with Soft Skills Moderation - Nina Fitriyah (GoodWill Journal of Economics, Management, and Accounting, 2024)
Education is a major pillar in national development, with schools playing a central role in shaping the nation's next generation through the provision of knowledge, skills, and values. The intense competition between private schools in Indonesia encourages them to improve their quality through effective management of Islamic education curriculum. This study examines the influence of Islamic education curriculum, family environment, and school environment on students' character, moderated by soft skills activities at SMA Labs School Kaizen Bogor. Using a descriptive quantitative approach, this study involved 65 randomly selected students. Data were collected through validated and reliable questionnaires and analyzed using SEM-PLS with Smart PLS 4 software. The findings of the study revealed that the Islamic education curriculum has a significant impact on students' character development, with the materials and values ​​contained therein contributing positively to their growth. The family environment also plays an important role, where the support and values ​​instilled at home significantly shape students' character. In addition, the school environment, which is characterized by a conducive learning atmosphere and positive interactions between students, teachers, and peers, significantly influences character formation. Soft skills activities further moderate the relationship between the Islamic education curriculum, family environment, and school environment, thereby increasing their influence on character development. This study underlines the importance of a holistic strategy involving curriculum, family, school, and soft skills in developing students' holistic character.